Europa in Basel - Lucas, Jana (Schwabe Verlag, 2018)
In her book, Jana Lucas portrays the artistic interchange in the context of the "Basler Konzil". For the first time, she provides an overall synopsis of the proceedings in art in the time of consiliar Basel.